Cognitive Abilities and Labour Market Outcomes: First Evidence for Germany - Silke Anger; Guido Heineck (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
We contribute to the literature on the relationship between cognitive abilities and labour market outcomes providing first evidence for Germany. In particular, cross-sectional data from the German Socio-Economic Panel (SOEP) are used, which include two measures of cognitive ability, one test of fluid mechanics (speed test) and another test of crystallised pragmatics (word fluency test). We find a positive relationship between cognitive abilities and economic activity, as workers with high ability test scores are less likely to be unemployed. In addition, results from Mincer-type OLS and 2SLS regressions suggest that mechanics abilities are correlated with wages in a significantly positive way for West German workers, even when educational attainment is controlled for, whereas pragmatics of cognition do not affect earnings significantly. However, we also find that ability and education are inseparable determinants of earnings, which confirms findings of recent studies for other countries.
Keywords: J31; I21; J24; 330; Cognitive ability; earnings regressions; returns to education; ability bias; unemployment probability